Antibiorésistance Et Facteurs De Virulence Des Souches D’escherichia Coli Isolées Des Carcasses Bovines Du Bénin - Ahouandjinou, Hélène; Baba-Moussa, Farid; Bertin, Gbaguidi; Sina, Haziz; Adéoti, Kifouli; Mousse, Wassiyath; Pouadjeu-Wouansi, Sylviane; Toukourou, Fatiou; Soumanou, Mohamed; Baba-Moussa, Lamine (European Scientific Journal, ESJ, 2016)
The meat processing conditions expose it to several contaminations including the microbial. The present study was designed to assess the antibiotic resistance and toxin production by Escherichia coli strains isolated bovine carcasses collected in the slaughterhouse of Cotonou / Porto-Novo in Benin. Thus, a total of 240 samples was collected from 60 beef carcasses by the destructive method. The E. coli strains were identified by conventional microbiological and biochemical methods. The susceptibility of strains to 15 antibiotics was assessed by disc diffusion method on agar medium. The phenotypic identification of strains producing penicillinase and BSLE was performed respectively by the tubes acidimetric test and the double halo method. PCR was used to detect genes encoding the toxins and β-lactamases. The results showed that 57.92% of the samples were contaminated with E. coli, with highest rate recorded in the samples collected from arm. The susceptibility to 15 antibiotics tested has shown that all the isolated strains were multi-resistant with a high proportion to ceftriaxone (88.49%). the lowest resistance rate ( 1%) was recorded with gentamicin. The E. coli strains producing β-lactamase carried multidrug resistance genes blaSHV (26.92%) and blaTEM (40.29%). To end, our data revealed the presence of EHEC pathovar (12.82%), responsible for the "traveler" disease. Thus, meat coming from slaughterhouses are therefore a potential source of food poisoning.